Intra-ACS trade : an overview of CDCC trade with non-CDCC groupings ([s.n.] [S.l.], 1996)
Examines trade flows between the various cooperation and integration groupings whose members are all members of the ACS, namely the Caribbean Development and Cooperation Committee (CDCC), the Central American Common Market (CACM) and the Group of Three. Examines the trade policies and other factors affecting intra-ACS trade, draws some conclusions and makes some policy proposals which may assist in the promotion of intra-ACS trade.
Draft